The long winter - Wilder, Laura Ingalls, 1867-1957.; Williams, Garth (New York : HarperTrophy, 1971)
After an October blizzard, Laura's family moves from the claim shanty into town for the winter, a winter that an Indian has predicted will be seven months of bad weather.
Newbery Honor Book, 1941.
Keywords: Wilder, Laura Ingalls, -- 1867-1957 -- Juvenile fiction; Wilder, Laura Ingalls, -- 1867-1957 -- Fiction; Frontier and pioneer life -- South Dakota -- Fiction; Families -- South Dakota -- Fiction; Blizzards -- Fiction; South Dakota -- Fiction